A systematic study of the genus Atlanticus Scudder, 1894 from Zhejiang, China (Orthoptera: Tettigoniidae: Tettigoniinae) - Liu, Xiao-Tong; Chen, Guang-Yu; Sun, Bi-Xuan; Qiu, Xiao-Feng; He, Zhu-Qing (Zootaxa, 2018)
Six species of genus Atlanticus have been recorded from Zhejiang, China prior to this study. We describe 2 new species, A. fallax sp. nov. and A. interval. sp. nov. Their morphology, songs, COI genes and distributions are compared. The type specimens are deposited in East China Normal University, Biology of History Museum (ECNU).